High-speed transmission characteristics of nonlinear spectral broadening carrier in turbulent channel - Tianshu WANG; Ying ZHANG; Ce YU; Fang DONG; Wanzhuo MA; Xianzhu LIU (Tongxin xuebao)
The nonlinear spectral broadening light source was used as a partially coherent carrier source with high repetition frequency to carry out experimental research on high-speed information transmission in atmospheric turbulence channels.A partially coherent beams source with nonlinear spectral broadening was obtained by pumping a highly nonlinear fiber with a picosecond fiber laser, and the repetition frequency could reach 10 GHz.The 10 Gbit/s pulse high-speed digital modulation was used and transmitted through a simulated atmospheric turbulence channel, the signal-to-noise ratio of the coherent optical carrier and partially coherent optical carrier before and after the turbulent channel transmission is reduced from 16.83 dB and 11.83 dB to 4.31 dB and 5.64 dB, respectively.In the simulated atmospheric turbulence channel at ∆T=230℃, when the bit error rate is 3.8×10-3, the sensitivity of partially coherent optical carrier links reaches-27.8 dBm, which is 1.6 dB higher than that of coherent optical carriers.